Preliminary Studies on Alkali-Activated Binder Based on Wood Waste Ash - Silveira e Silva, André Augusto (2023)
Alkali-activated binders (AAB) are inorganic materials produced by a mixture between a solid precursor and an alkaline activator, wherein, the reaction results in a material with properties similar to Portland cement hydration. The advantages of AAB over Portland cement are the possibility of using alternative materials, demanding low energy and low CO2 emission. The primary objective of this study was to produce an alkali-activated binder (AAB) using calcined wood waste ash (CWWA) as a solid precursor due to its beneficial properties. CWWA was obtained by burning wood wastes in a furnace, then calcined in a laboratory oven at 600 °C to remove unburned particles. Afterward, the ash was milled and then physiochemically characterized by chemical composition, X-ray diffraction (XRD), particle size distribution, and scanning electron microscopy (SEM). The milled CWWA was employed in AAB mortars and pastes activated with sodium hydroxide (NaOH) to assess the influence of alkaline activator concentration. In this work, the Na+ concentrations varied in the 6.5-12.5 mol.kg-1 range. Mortars were assessed by compressive strength, whereas pastes were analyzed by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), and scanning electron microscopy/energy-dispersive X-ray spectroscopy (SEM/EDS) for samples cured after 7 days at 60 °C. Results showed that the CWWA is mainly composed of SiO2 (67.9 wt%) and the presence of an amorphous phase and quartz as the main crystalline phase (XRD). The compressive strength of mortars showed that the CWWA activated with a Na+ concentration of 6.5 ml.kg-1 achieved the highest compressive strength (23.2 ± 1 MPa). Microstructural studies of pastes showed the formation of sodium carbonate (XRD) and reaction products (FTIR) in a dense microstructure (SEM/EDS). Hence, the key findings suggest that employing CWWA as a solid precursor offers a viable choice for producing a more sustainable AAB.